Sustainable drive tourism routes: a systematic literature review - Cruz, Sandra (2022)
Drive tourism (DT) has become an attractive way to visit tourism destinations for an increasing number of visitors along driving routes. This flow of visitors has made sustainability a major issue, that is, the way by which tourism development ensure economic benefits for local communities and preserves local identity, along the route, without compromisingtheenvironmental resources. Many studies focused the topic of DT, mainly the analysis of a particular angle, either be economic sustainability, e.g., advantages of the ones related to economic and environment sustainability, such as the impact of tourists along the route environment. Nevertheless, little attention has been paid to the social consequences of DT in the local entrepreneurial environment and the resulting exaggeration of their cultural representativeness in the sense of authenticity. Our aim is to summon these points of view and achieve, through a systematic literature review, a clear and integrative picture of the driving tourism impacts in terms of sustainability along the routes throughout local communities. A systematic literature review was performed using the PRISMA guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology. This systematic literature review sought to consolidate knowledge on the subject. In order to illustrate the link between major categories and their corresponding trends, authors used VOSviewer scientific software. The gathering of existing knowledge around the three components of sustainability highlighted the importance of community involvement and collaboration among DT stakeholders to address the trade-off between the protection and promotion of DT routes. Opportunities for future studies are suggested.